The Effect of Consumption of Kepok Banana (Musa Paradisiaca Formatipyca) on Reducing the Intensity of Nausea, Vomiting in 1st Trimester Gravida Women - Suci Anggraeni; Luvi Susiana; Reni Yuli Astutik; Nining Istighosah; Yenny Puspitasari (Journal of Nursing Practice)
Background: Nausea and vomiting in early pregnancy is something that is normal for all pregnant women to experience as long as the intensity is not excessive. This has an impact on pregnant women and also the fetus, causing fluid, nutrition and weight loss.